Experience with Devices implanted fixed-rate pacemakers. Issue 2 (March 1973) - Siddons, Harold; Davies, Geoffrey
Abstract : The fate of 183 implants of Devices TF 2970 fixed-rate pacemakers is analysed. The incidence of clinical complications such as sepsis or skin necrosis, displacement of the electrode, and exit block, and the causes of the 19 deaths are discussed. In 28 of the 183 pacemakers pacing stopped for technical reasons, which are described; the commonest cause of failure was the batteries. The incidence of pacemaker failure has been estimated statistically from a much larger series of 558 implants.